Predicting Lung Health Trajectories for Survivors of Preterm Birth - Gibbons, James T. D.; Wilson, Andrew C.; Simpson, Shannon J. (Frontiers in Pediatrics, 2020)
Rates of preterm birth (<37 weeks of gestation) are increasing worldwide. Improved perinatal care has markedly increased survival of very (<32 weeks gestation) and extremely (<28 weeks gestation) preterm infants, however, long term respiratory sequalae are common among survivors. Importantly, individual’s lung function trajectories are determined early in life and tend to track over the life course. Preterm infants are impacted by antenatal, postnatal and early life perturbations to normal lung growth and development, potentially resulting in significant shifts from the “normal” lung function trajectory. This review summarises what is currently known about the long-term lung function trajectories in survivors of preterm birth. Further, this review highlights how antenatal, perinatal and early life factors are likely to contribute to individual lung health trajectories across the life course.